Exposition March - Leo Friedman::::::::: (Frank K. Root & Co.)
Piano score, 6 p. Cover title: Exposition march, San Francisco, 1915. On cover is lithograph of drawing of a tower with a grand staircase (never built). Publishers advertisements on p.[2] and verso of last leaf.